Randomized Clinical Trial: Bergamot Citrus and Wild Cardoon Reduce Liver Steatosis and Body Weight in Non-diabetic Individuals Aged Over 50 Years - Ferro, Yvelise; Montalcini, Tiziana; Mazza, Elisa; Foti, Daniela; Angotti, Elvira; Gliozzi, Micaela; Nucera, Saverio; Paone, Sara; Bombardelli, Ezio; Aversa, Ilaria; Musolino, Vincenzo; Mollace, Vincenzo; et al. (Frontiers in Endocrinology, 2020)
Background: Non-alcoholic fatty liver disease is the most common cause of liver-related morbidity and mortality in the world. However, no effective pharmacological treatment for this condition has been found. Purpose: This study evaluated the effect of a nutraceutical containing bioactive components from Bergamot citrus and wild cardoon as a treatment for individuals with fatty liver disease. Methods: A total of 102 patients with liver steatosis were enrolled in a double-blind placebo controlled clinical trial. The intervention group received a nutraceutical containing a Bergamot polyphenol fraction and Cynara Cardunculus extract, 300 mg/ day for 12 weeks. The control group received a placebo daily. Liver fat content, by transient elastography, serum transaminases, lipids and glucose were measured at the baseline and the end of the study. Results: We found a greater liver fat content reduction in the participants taking the nutraceutical rather than placebo (-48.2 ± 39 vs -26.9 ± 43 dB/m, p=0.002); The percentage CAP score reduction was statistically significant in those over 50 years, or in overweight / obese individuals. Body weight significantly decreased in both groups (-2.7 ± 2 vs -4.2 ± 3 kg in placebo and nutraceutical respectively p=0.004). Conclusions: A nutraceutical containing bioactive components from Bergamot and wild cardoon reduces the liver fat content in individuals with liver steatosis and could become the cornerstone treatment of patients affected by liver steatosis. Clinical Trial Registration: www.isrctn.com, identifier ISRCTN12833814